A patient with odynophagia and unusual endoscopic findings. (26th November 2015) - Griffin, Jessica; Potts, Jonathan; Chatu, Sukhdev; Chung-Faye, Guy
Abstract : The case describes a 50-year-old woman presenting with a severe painful dysphagia to solids, impacting on her nutritional intake. She had a history of pemphigus vulgaris maintained in remission with azathioprine, with no evidence of active oral or cutaneous disease at the time of presentation. Endoscopy and histology from the distal oesophagus revealed oesophageal involvement of pemphigus vulgaris. This is a relatively rare clinical form of the disease, with only 58 cases reported worldwide. Patients with pemphigus vulgaris are also prone to infective or steroid-induced gastritis, which present in the same way. Early endoscopic evaluation is therefore essential to distinguish between oesophageal involvement of pemphigus vulgaris and other pathologies, which warrant significant differences in management.